Implementing Combined FEFO and FIFO Methods in Inventory System (Case Study: UD Ilham Pilly Beef Merchant) - Ramadhan, Ilham; Usman, Ari; Sarudin, Sarudin (Universitas Negeri Medan, 2023)
Stock inventory is an important aspect of supply chain management. The success of the company's operations in maintaining stock availability and avoiding losses due to damage or expiration of goods is very dependent on the use of the right method of managing inventory. The purpose of this study is to combine the FEFO (first expired first out) and FIFO (first in first out) methods in the UD. Ilham Pilly Beff Merchant stock inventory system to avoid losses due to expired goods and increase stock rotation because the FEFO and FIFO methods are operational management in determining inventory. The results of this study are that the system that has been designed can facilitate managers in the process of collecting data on incoming and outgoing goods so that the risk of managing product stocks can be minimized and with an inventory system that has been built